History of the gun in 500 photographs. (New York, New York : Liberty Street, an imprint of Time-Life Books, 2016)
A fascinating look into the history of the firearm and how and why it has had the impact it has on American culture and society. Few inventions have had more of a profound impact on the course of civilization than guns: The first hand-held versions were Chinese fire lances invented in the 10th century, though it was Europeans who were credited with creating the handheld weapons that we recognize today. Americans and their expansion westward were the ones who refined, and helped define innovation and the development of an industry. Starting with Samuel Colt and the "revolver revolution," Americans took the lead in moving gun development forward. Names now well-known including Wesson, Winchester, and Browning helped create weapons that helped move a nation forward and ushered in the industrialized warfare of World War I. Now, TIME-LIFE, in the next book in the success "500 Photographs" series, following World War II in 500 Photographs and The Civil War in 500 Photographs , brings readers The History of the Gun in 500 Photographs , which traces the fascinating evolution of firearms, not just as tools of security, but as ingenious feats of science and engineering. This book contains over 500 photos that take readers on a historical and visual journey of the gun, not just as a weapon, but as a constantly-evolving artifact that has shaped America's culture and mindset.
-- Black powder, alchemy, and bombards -- Matchlocks and muskets -- An era of experimentation -- Coming to America -- The road to the revolver -- The Civil War and the rise of the rifle -- Firearms and the Wild West -- World War I and Industrialized warfare -- World War II: A great generation of guns -- Modern times, new materials.
Includes index.
Keywords: Firearms -- History